Neuron-associated retroelement-derived protein Arc/Arg3.1 assists in the early stages of alphaherpesvirus infection in human neuronal cells - Kobayashi, Hiroko; Yasukochi, Mitsuki; Horie, Masayuki; Orba, Yasuko; Sawa, Hirofumi; Fujino, Kan; Taharaguchi, Satoshi (PloS one, 2024)
Alphaherpesviruses, including herpes simplex virus type 1 (HSV-1) and pseudorabies virus (PRV), are neurotropic double-stranded DNA viruses. Alphaherpesviruses control the expression of various host factors to ensure efficient infection and propagation. Recently, HSV-1 was found to upregulate Arc/Arg3.1 (Arc) expression, which is a retroelement-derived domesticated gene. Arc is associated with learning and neuroplasticity in host neuronal cells, and its abnormal expression leads to neurological disorders. However, the detailed mechanisms underlying the upregulation of Arc and its physiological significance in viral infections remain unclear. In this study, we found that PRV infection upregulated Arc expression in vitro and identified ICP0 and EP0, the transcriptional regulatory genes of HSV-1 and PRV, as triggers for enhanced Arc expression. Mass spectrometry and co-immunoprecipitation assays identified VP5, the major capsid protein of PRV and HSV-1, as the viral factor that interacted with Arc. Arc knockdown delayed viral infection during the early stages of the viral life cycle, but did not impact the viral attachment and entry. In conclusion, we provide evidence that alphaherpesvirus ICP0 homologues control Arc expression. Additionally, we demonstrate that Arc interacts with the major capsid protein VP5 and plays an important role in the viral lifecycle after intracellular entry. This study advances our knowledge of herpesvirus and retroelement-derived Arc interactions, providing fundamental insights into the pathogenesis of retroelement-derived domesticated genes and herpesvirus-induced neurological diseases.